Islamic Tolerance Values in the Digital-based Teaching for Elementary School in Cirebon City - Farihin Farihin (UIN Sultan Aji Muhammad Idris Samarinda, 2022)
This paper aims to find out how the implementation of Islamic-based tolerance values in Digital-Based Elementary Schools, supporting and inhibiting factors, and success in implementing Islamic-Based tolerance values in Digital-Based Elementary Schools in Cirebon City West Java, Indonesia. This writing is a qualitative descriptive writing with a phenomenological approach. Data in this paper was collected using observation techniques, in-depth interviews, documentation, and triangulation. Meanwhile, to analyze the data obtained, the author uses data reduction, data presentation, and data verification. Based on the research results, the implementation of Islamic-based tolerance values in Digital-Based Elementary Schools in Cirebon City is carried out by: 1) provide opportunities for all students to take part in religious learning in accordance with their respective religious beliefs; 2) fostering a tolerant environment in all classes (learning about differences, fostering mutual trust, upholding mutual understanding, and upholding mutual love); and 3) fostering a deeper understanding of Islam among students (tolerance value). Government policies that provide guidelines for advancing the ideals of religious tolerance, adequate facilities, and the realization of collaboration between students in religious activities are all supporting aspects. Ability level, differences in students' emotional maturity, lack of resources (such as learning media), and lack of time to learn are some of the variables that hinder learning.